Kombucha Tea Production by Amobil Cells in Several Different Tea Processing - I. Irdawati; Putri Alamanda Sari (Bioscience, 2020)
Kombucha is a fermented tea made from steeping tea and sugar which utilizes byproducts from bacterial and yeast symbiosis in the form of acidic compounds and nata (cellulose). Kombucha fermentation process produces a variety of substances that are efficacious to improve body health and ward off poisons. One method of kombucha fermentation can be done by cell immobilization method or enzymes because it can be repeated fermentation. The purpose of this study was to determine the quality of kombucha tea by immobilized cells in several different teas.This research is an experimental research. The research was conducted from May - August 2019 in the Microbiology Laboratory of the Faculty of Mathematics and Natural Sciences, Padang State University. The quality test of kombucha tea by immobilized cells can be determined by measuring the thickness of nata, pH, and total acetic acid of Kombucha tea. Data were analyzed using ANOVA followed by further tests DMRT with a level of 5%. The results showed that the best quality of kombucha tea by immobilized cells was green tea with a thickness of 0.53 cm nata, pH 5.62 and total acetic acid (%) 4.40.